Deconstruction and the Archival Revolution: on the Relevance and Reception of Archive Fever in New Media Studies - Glavaš, Zvonimir (Poznańskie Studia Slawistyczne, 2020)
The paper focuses on the reception of Derrida’s Archive Fever among (new) media theorists and its relevance for the ongoing discussions in that academic field. Although this Derrida’s text is often described as the one in which he provides a statement on the pervasive revolutionary impact of new media, its reception among media theorists remains scarce. Several media scholars that tackle the text, however, have an ambivalent stance on it: they appreciate some of Derrida’s theses, but regard them largely obsolete. The first part of the paper analyzes these critiques and argues that many of the objections on Derrida’s behalf are caused by the misinterpretation of important features of the deconstructive thought. In its second part, the paper firstly deals with certain weaker points of Derrida’s reflection and then proceeds to examine his insights pertinent to the problems of contemporary media theory that were neglected in earlier reception. Finally, paper reaffirms the claim about the need for a more profound exchange between the deconstruction and media studies, albeit one that would avoid the examined shortcomings.